Answer: 10
=====================================================
Work Shown:
Plug in n = 1 to find the next term
f(n+1) = f(n) - 2
f(1+1) = f(1) - 2 ... replace every n with 1
f(2) = f(1) - 2
f(2) = 18-2 .... replace f(1) with 18
f(2) = 16
We'll use this to get the next term. Plug in n = 2
f(n+1) = f(n) - 2
f(2+1) = f(2) - 2 ... replace every n with 2
f(3) = f(2) - 2
f(3) = 16 - 2 ... replace f(2) with 16
f(3) = 14
This process keeps going until we reach f(5)
Plug in n = 3
f(n+1) = f(n) - 2
f(3+1) = f(3) - 2
f(4) = f(3) - 2
f(4) = 14-2
f(4) = 12
and finally plug in n = 4
f(n+1) = f(n) - 2
f(4+1) = f(4) - 2
f(5) = f(4) - 2
f(5) = 12 - 2
f(5) = 10
The summary is basically we subtract 2 from each term to get the next term. The sequence is 18, 16, 14, 12, 10 which is arithmetic.